ICT and primary mathematics - Williams, John, 1936- (RoutledgeFalmer, 2004)
This book, written for practising teachers and student teachers, will demonstrate how ICT can be used to develop and enhance investigative primary mathematics.
Keywords: Mathematics -- Computer-assisted instruction.; Mathematics -- Study and teaching (Primary) -- Data processing.; Educational technology.; Mathématiques -- Enseignement assisté par ordinateur.; Technologie éducative.; EDUCATION -- Teaching Methods & Materials -- Mathematics.; Educational technology; Mathematics -- Computer-assisted instruction